PENGARUH KUALITAS PRODUK,KUALITAS PELAYANAN DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT BELI DI ARJUNA LAPTOP SURAKARTA - Khasannudin Yusuf; Sri Isfantin Puji Lestari; MG Sukamdiani (JURNAL ILMIAH EDUNOMIKA, 2025)
This research investigates how product quality, service quality, and consumer trust influence customers’ purchase intention. The study focuses on these three independent variables in relation to purchase intention as the dependent variable. Data were obtained through questionnaires distributed to customers of Arjuna Laptop Surakarta who had made at least two purchases. Using a purposive sampling technique, 100 respondents were selected as the sample. The data analysis involved validity and reliability testing, multiple linear regression, and hypothesis testing through t-test, F-test, and the coefficient of determination (R²).Findings reveal that product quality, service quality, and consumer trust each exert a positive and significant partial influence on purchase intention. When tested simultaneously, the three variables also show a positive and significant overall effect. Interestingly, the most dominant factor influencing purchase intention is consumer trust, rather than product quality, as reflected by the regression coefficients (b₃ = 0.352 > b₂ = 0.286 > b₁ = 0.280). The coefficient of determination (R²) value of 0.447 indicates that 47.7% of the variation in purchase intention can be explained by the three independent variables, while the remaining 52.3% is influenced by other factors beyond the model. Keywords : Kualitas Produk, Kualitas Pelayanan, Kepercayaan Konsumen,Minat Beli